Influence of cavosurface angle on the stress concentration and gaps formation in class V resin composite restorations - Correia, Ayla Macyelle de Oliveira [UNESP]; Pereira, Victoria Elisa Maciel [UNESP]; Bresciani, Eduardo [UNESP]; Platt, Jeffrey A.; Borges, Alexandre Luiz Souto [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Elsevier, 2019)
The study aimed to evaluate the influence of cavosurface angle on stress concentration and gap formation in class V restorations. Cylindrical cavities 3 mm in diameter were prepared in forty-five bovine incisors, changing only the angle of the bur in relation to the flat surface of the tooth. The cavities maintained the same volume (17.67 mm³). The samples were divided according to the cavosurface angle, into three groups (n = 15): 90°, 120°, 135°. After adhesive application (Futurabond U, VOCO), the cavity was filled with bulk placement of a resin composite (GrandioSO, VOCO). The teeth were analyzed with stereomicroscopy. Data of marginal gap formation were statistically analyzed with a one-way analysis of variance (ANOVA) followed by Tukey tests (significance level: α = 0.05). Finite element analysis (FEA) was used to study residual stress in these geometries and to correlate those stresses with experimentally measured gap formation. The elastic modulus and polymerization shrinkage were determined for FEA. Residual shrinkage stresses were expressed in maximum principal stress (MPS). There was a significant difference in the gap formation among the groups (p = 0.001). A significantly lower marginal gap formation was found for 120° and 135° angles, with no significant difference between them. The cavosurface angle at 90° caused substantially higher stresses, in the restoration interface, with greater marginal gap. For the 120° and 135° angles, the stress concentrations were smaller and were located in the dental structure. The cavosurface angle influenced the marginal gap formation and stress concentration.
Keywords: Cervical lesion; Composite resins; Dental marginal adaptation; Finite element analysis; Residual stress